(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
We study an iterative scheme to approximation the split common null point problems for set-valued maximal monotone operators which combine viscosity method and some fixed point technically proving method between Banach spaces and Hilbert space, without using the metric projection. We prove that strong convergence theorem. Also, we show that our result can be solves the split minimization problems.